Subclinical patterns of cardiac involvement by transthoracic echocardiography in individuals with mild initial COVID-19 - Anastasia Shchendrygina; Mame Madjiguène Ka; Carlos Rodriguez; Safaa Alsoufi; Jedrzej Hoffmann; Parveen Kumar; Maria Ludovica Carerj; Byambasuren Vanchin; Niels Holm; Argyro Karyou; Mijidsuren Ganbat; Eike Nagel; et al. (Scientific Reports)
Abstract The aim of this study was to evaluate the subclinical patterns and evolution of cardiac abnormalities via transthoracic echocardiography (TTE) in patients with mild initial COVID-19 illness. A total of 343 infected individuals (163 males; age 44 (interquartile range, IQR 35–52) years) years) underwent serial TTE assessments at a median of 109 (interquartile range (IQR), 77–177) and 327 (276–379) days after infection. Compared with those of non-COVID-19-infected controls (n = 94, male n = 49), baseline systolic (LVEF, TAPSE) and diastolic function (eʹ, aʹ, E/eʹ) were significantly different in infected participants (p < 0.05 for all). Compared with baseline assessments, there was a reduction in global longitudinal strain (GLS) and an increase in the E wave, E/A ratio and E/eʹ at follow-up. At baseline, symptomatic participants had a lower LVEF and TAPSE and increased IVRT, eʹ and E/eʹ. At follow-up, symptomatic patients had a lower LV end-diastolic diameter (LVEDd). Symptoms were independently associated with E/eʹ at baseline (OR (95% CI) 1.45 (1.12–1.87), p = 0.005). Symptoms at follow-up were associated with LVEDd, measured either at baseline (OR: 0.91 (0.86, 0.96), p < 0.001) or follow-up (OR (95% CI) 0.91 (0.86–0.96), p < 0.001). There were significant associations for GLS and troponin and E/eʹ with CRP and NTproBNP at baseline. In the present cohort of COVID-19-infected individuals with mild initial illness, echocardiographic measurements revealed significant yet subclinical differences in systolic and diastolic function compared with controls, as well as between individuals with cardiac symptoms and those without. All the measured differences were small in magnitude and thus unlikely to be detectable clinically at the individual level.